Evaluation and participatory variety selection of improved highland sorghum varieties for smallholder farm at west hararghe zone - Temesgen Begna; Hailu Gichile (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Participatory variety selection is the most important breeding program which enhanced the adoption of improved varieties through creating awareness based on smallholder farmers' selection criteria. Several different improved sorghum varieties are released at different international and national research institutions at different times, however, the technologies were not properly addressed the farmers based on participatory, client oriented and demand driven. The experiment was carried out in West Hararghe Zone; Oromia Regional State, Ethiopia with the objective to identify and recommend the best adapted and performed improved sorghum varieties with farmers' preference traits through continuous performance evaluation at different stages of the sorghum. A total of six sorghum varieties were evaluated in randomized complete block design in the 2019 main cropping season. Farmers have evaluated the entire experimental units using different statistical tools like direct-matrix and pair-wise ranking algorithms at maturity stage. Farmers set selection criteria to identify the superior improved varieties as compared to the local check by listing different agronomic traits like yield, biomass, seed color, seed size and biotic and abiotic resistance. The analysis of variance showed that there was highly significant difference (p<0.01) among the genotypes for all studied traits. The greatest grain yield was recorded from the variety Dibaba (11325 Kgha-1) and Jiru (10200 Kgha-1) respectively. Likewise, based on the overall farmer's preference, Dibaba and Jiru were ranked first and second and followed by Adelle, ETS2752 and Chiro respectively. Additionally, the study revealed that participatory varietal selection is playing decisive role in gathering farmers' perceptions, preferences, merits and shortcomings of sorghum varieties for future improvement. Hence, based on the result of the study, variety Dibaba and Jiru were recommended for multiplication and distribution to farmers through both formal and informal seed systems. Generally, the integration of plant breeders and farmers' perceptions are used to increase the adoption rate and design a good breeding program for future improvement.